STRATEGI GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KEDISIPLINAN SISWA DI MAN 1 BANJARMASIN - Noviaty, Dessy; Yuliansyah, M; Fauzi, Zainal (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2018)
This research was carried out based on the phenomenon that occurred in MAN 1 Banjarmasin lack of discipline in these students quite happened in school, students who were late coming to school, dressed not according to the rules, often did not go to school and this is often complained by subject teachers and teachers other teacher. In this case it is necessary to involve teachers in guidance and counseling in dealing with students who are less disciplined. The formulation of the problem in this study is how to improve student discipline and whether the teacher's guidance and counseling strategies will be used in improving student discipline. The objectives to be achieved in this study want to know the teacher's guidance and counseling strategies and what strategies will be used. This research was conducted by interviewing all the guidance and counseling teachers in MAN 1 Banjarmasin as informants. The method used was qualitative method. The conclusion was that the guidance and counseling teacher had a strategy in improving student discipline because the guidance and counseling teacher or commonly called counselor had responsibility full in improving student discipline. Guidance and counseling teachers choose individual counseling strategies because specifically personal counseling between a counselor and students. In this individual counseling it is expected that the counselee can change attitudes, self-decisions so that students can better adapt themselves and the surrounding community. Keywords: BK Teacher Strategy; Discipline; Students.